The effects of grazing on daily caloric intake and dietary quality - Eliana Zeballos; Carolyn Chelius (BMC, 2021)
Abstract Background The duration and frequency of eating occasions has been identified as a factor contributing to poor dietary quality among U.S. adults. The objective of this study is to examine whether grazing, defined as eating more than three times a day, affects total daily caloric intake and dietary quality measured by the 2015 Healthy Eating Index (HEI-2015). Methods We used a multivariate individual fixed-effects model to compare the caloric intake and dietary quality of individuals who grazed on 1 day but not another. This allowed us to control for differences in individual food intake and diet quality preferences among study participants. We use the National Health and Nutrition Examination Survey (NHANES), 2007-2018, and include data for adults aged 18 years or older who reported 2 days of dietary intake and were not pregnant or lactating (n = 27,775). Results Grazing increased total daily caloric intake by 205 cal and increased the daily HEI score by 0.59 points. Grazing increased HEI component scores for total fruit, whole fruit, and refined grains, and decreased HEI component scores for saturated fats. Morning grazing increased total daily caloric intake by 159 cal and increased the daily HEI score by 0.87 points - primarily by increasing component scores for total fruit, whole fruit, whole grains, total dairy, seafood and plant proteins, and sodium. Evening grazing increased daily caloric intake by 76 cal and decreased the daily HEI score by 0.41 points - primarily by decreasing the component scores for total fruit, whole grains, fatty acids, and saturated fats. Evening grazing increased HEI component scores for sodium and refined grains. Conclusions Grazing increases daily caloric intake and can decrease dietary quality (particularly when grazing in the evening).